Periodontal Care In Prolanis Diabetics: Sungai Ulin and South Banjarbaru Primary Health Care Study - Naning Kisworo Utami; Metty Amperawati; Rasuna Ulfah; Bunga Nurwati; Hammad (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
The research focused on oral health among diabetes mellitus patients, particularly in preventing periodontal disease within the prolanis group. Using analytical descriptive methods, the study evaluated oral cavity abnormalities. Findings at Sungai Ulin and South Banjarbaru Community Health Centers revealed a significant number of respondents with tartar and shallow gum pockets, indicating a substantial need for care. The majority scored 2 on the CPITN scale (61.8%), underscoring the demand for attention from healthcare providers including community health workers, dentists, and dental nurses. Recommendations stress the pivotal role of oral health maintenance for diabetes mellitus individuals. These suggestions encompass regular blood sugar monitoring, consistent dental hygiene, tartar removal, denture care, and eliminating local factors causing gum infections. Periodontal disease's impact on daily life includes chewing difficulties, speech impediments, and tooth loss, accentuating the urgency of preventive measures for diabetes mellitus patients. In summary, proactive preventive actions are crucial to address periodontal disease among diabetes mellitus individuals, aiming to diminish its occurrence and improve their overall well-being and quality of life.